Discovery and development of single-nucleotide polymorphism markers for resistance to Striga gesnerioides in cowpea (Vigna unguiculata) - Ongom, Patrick Obia; Fatokun, Christian Ademola; Boukar, Ousmane (Frontiers in Plant Science, 2025)
IntroductionThe parasitic weed [Striga gesnerioides (Willd.) Vatke] is a principal biotic constraint to cowpea [Vigna unguiculata (L.) Walp.] production in West and Central Africa, causing severe yield reductions. Multiple races of S. gesnerioides exist across the cowpea-growing areas of the sub-region. Past efforts identified some resistant sources and race-specific genes underpinning Striga resistance, but deployment of associated markers in breeding is limited. Here, we utilized a 51K cowpea iSelect single-nucleotide polymorphisms (SNPs) to decipher genomic regions underlying Striga resistance and explore marker conversion and validation for easy deployment.MethodThe study used two-year phenotypic data on a minicore panel of 368 cowpea genotypes screened at two sites in Northern Nigeria. SNPs performances were verified and validated using two independent sets of 60 and 20 diverse genotypes respectively.ResultsThe minicore displayed apparent differences in response to the S. gesnerioides attack. A genome-wide scan uncovered a primary gene effect signal on chromosome Vu11 and minor regions on chromosomes Vu02, Vu03, Vu07, Vu09 and Vu10. The major effect region on Vu11 harbored a coil-coil nucleotide-binding site leucine-rich repeat (CC-NBS-LRR) protein, encoded by the RSG3–301 gene, previously implicated in race-specific resistance to S. gesnerioides in cowpea. The associated SNPs were successfully converted into Kompetitive Allele-Specific PCR (KASP) assays and validated using 20 independent diverse cowpea genotypes. Five KASP markers, snpVU00075, snpVU00076, snpVU00077, snpVU00078, and snpVU00079, depicted consistent and significant associations with the phenotype in the validation set.DiscussionThe markers provide valuable tools for efficient marker-assisted selection (MAS) in breeding programs focused on developing Striga-resistant cowpea varieties.